Population dynamics of Myzuspersicae (Sulzer) on intercropping potatoes with other plants on Karo Highland - Lamria Sidauruk; Darma Bakti; B. Sengli J. Damanik; Retna Astuti Kuswardani (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2013)
Green peach aphid (MyzuspersicaeSulze) represents one of the major pest affecting decreased production which found in different potato fields in Karo highland. Decreasing incurredin two ways: the direct damages that are caused by the insectfeeding on the plants and the indirect damages caused to potato planting materials as a virus vector. There are different methods for controlling green peach aphids, all of them relying inthe use of chemicals and this method makes food production contaminated by pesticide residu. So, using non-chemical methods of cultivation contribute to “ecological” food production.Intercropping is one way of reducing pest insect populations in such vegetable crops.This study was conducted to determine the population dynamics of Myzuspersicae (Sulzer) on Intercropping system of potato plant with other vegetables plant on Karo Highland. The host plant was cultivar Granola of potato and the intercropping plant respectively were cabbage, mustard, celery, onions, carrot and bean. The results showed that M. persicae was consistently at different densities in different intercropping plant on potato. The aphid was first recorded at three week until planting. The kind of inter cropping culture plants significantly reduced the number of aphid. The lowest number of aphid found respectively inintercroppingpotatoesandmustard, potatoesandonions, andpotatoesandcelery. There was 0.80 aphids /leaf, 1,12aphids/leaf, 1,48 aphids/leaf. At the 2nd observation found the number of aphid was lowest atpolyculture potatoes and mustards were 1,68 aphid/leaf, at popatoes and onions were 3,28 aphid/leaf, at popatoes and celery 3,00 aphid/leaf. The number of aphids steadily increased with significant at differencesintercroppingplant till the 3rd observation (9 weeks until planting) respectively where 2,80aphid/leaf, 3,42 aphid / leaf and 4,20 aphid/leafwere recorded. Observation for natural enemies of M. persicaeshowed that fewnatural enemiesfound in theagro-ecosystem. There are Episyrphusbalteatus, Chrysoperlacarnea, phidiusmatricarieae and Coccinellaseptempunctata. The population density of all of the natural enemies was highest at polyculture than monoculture of potato. After that, as the population of M. persicae started decline, the same trend was followed by all of its natural enemies.